186k views
1 vote
(-3+2iroot48)(-5-4iroot12)

User Ant
by
6.3k points

1 Answer

4 votes

For this case we must simplify the following expression:


(-3 + 2i \sqrt {48}) (- 5-4i \sqrt {12})

Rewriting:


(-3 + 2i \sqrt {4 ^ 2 * 3}) (- 5-4i \sqrt {2 ^ 2 * 3}) =\\(-3 + 2 * 4i \sqrt {3}) (- 5-4 * 2i \sqrt {3}) =\\(-3 + 8i \sqrt {3}) (- 5-8i \sqrt {3}) =

We apply distributive property:


- * - = +\\- * + = -\\15 + 24i \sqrt {3} -40i \sqrt {3} - (8i \sqrt {3}) ^ 2 =\\15 + 24i \sqrt {3} -40i \sqrt {3} -64i ^ 2 * 3 =

We have to
i ^ 2 = -1:


15 + 24i \sqrt {3} -40i \sqrt {3} + 192 =

Adding similar terms:


207-16i \sqrt {3}

Answer:


207-16i \sqrt {3}

User Tausun
by
5.3k points